2018
DOI: 10.1186/s12885-018-4839-y
|View full text |Cite
|
Sign up to set email alerts
|

The BETTER WISE protocol: building on existing tools to improve cancer and chronic disease prevention and screening in primary care for wellness of cancer survivors and patients – a cluster randomized controlled trial embedded in a mixed methods design

Abstract: BackgroundThere is a pressing need to reduce the burden of chronic disease and improve healthcare system sustainability through improved cancer and chronic disease prevention and screening (CCDPS) in primary care. We aim to create an integrated approach that addresses the needs of the general population and the special concerns of cancer survivors. Building on previous research, we will develop, implement, and test the effectiveness of an approach that proactively targets patients to attend an individualized C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…The aim of BETTER WISE is to determine if patients aged 40 to 65, including patients with and without a cancer history (breast, colorectal, and/or prostate), randomized to receive an individualized prevention visit with a PP improve cancer surveillance and prevention and screening outcomes. The primary outcomes are measured at the patient level and determined by a composite index, as compared to standard care in a wait-list control group twelve months after the initial prevention visit (Manca et al, 2018). In the BETTER 2 implementation study, we found that physicians' opinions on the BETTER prevention visits deviated from the opinions of PPs and patients (Sopcak et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The aim of BETTER WISE is to determine if patients aged 40 to 65, including patients with and without a cancer history (breast, colorectal, and/or prostate), randomized to receive an individualized prevention visit with a PP improve cancer surveillance and prevention and screening outcomes. The primary outcomes are measured at the patient level and determined by a composite index, as compared to standard care in a wait-list control group twelve months after the initial prevention visit (Manca et al, 2018). In the BETTER 2 implementation study, we found that physicians' opinions on the BETTER prevention visits deviated from the opinions of PPs and patients (Sopcak et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…PPs were also trained and certi ed in Brief Action Planning (Gutnick et al, 2014;Reims et al, 2018), which "is grounded in the principles and practice of Motivational Interviewing and behaviour change theory and research, emphasizing compassion, acceptance, partnership and evocation" (Centre for Collaboration, Motivation & Innovation, 2019), in order to guide patients towards healthy lifestyle modi cation and behaviour change, and collaboratively set S.M.A.R.T. (speci c, measurable, attainable, realistic, time-based) lifestyle or screening-related goals (Manca et al, 2018).…”
Section: Study Settingmentioning
confidence: 99%
See 3 more Smart Citations